A highly sensitive aptasensor for on‐site detection of lipopolysaccharides in food. Issue 6 (2nd September 2018) - Cheng, Cheng; Wu, Jayne; Chen, Jiangang
Abstract: A rapid, low‐cost, highly sensitive, and specific capacitive aptasensor is presented for detection of lipopolysaccharides (LPS). Exposure to LPS could cause fever, gram‐negative sepsis, septic shock, and eventual death. Hence, rapid, low cost, and sensitive detection of LPS is pivotal for the safety of food, pharmaceutical, and medical devices and products. In this work, a capacitive sensing method based on alternating current electrokinetics is developed to achieve rapid and specific detection of LPS. This method uses an alternating current signal for two purposes. One is to induce positive dielectrophoresis, which attracts LPS toward the sensor electrodes' surface and accelerates its binding with the immobilized aptamer probe. The other purpose is to simultaneously sense the binding reaction by measuring the interfacial capacitance change on the electrodes' surface. The testing procedures and instrumentation setup of this sensing platform are significantly simplified while finding quantitative concentrations of both analytical and complex samples within 30 s. When testing analytical samples of LPS from Escherichia coli O55:B5, a LOD of 4.93 fg/mL is achieved. The recovery analysis is also performed with LPS spiked in a complex matrix and good recovery rates are demonstrated. This work provides an affordable and field‐deployable platform for highly sensitive and real‐time LPS detection.